The Influence of Business Model Canvas on Financial Performance of Micro, Small, and Medium Enterprises (MSMEs) - Susanti, Diah Ayu; Fithri, Diana Laily; Gunawan, Budi; Budiman, Nita Adriyani; Mulyani , Sri; Nugraha, Fajar (Journal of Ecohumanism, 2024)
This research aimed to analyze the influence of the nine components of Business Model Canvas (BMC) on financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Kudus Regency. BMC components included Customer Segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure. In addition, the data was collected from 393 MSMEs selected through purposive sampling using a quantitative method. The analysis was performed using Structural Equation Modeling (SEM) and SmartPLS 3 software. The results showed that Cost Structure had a positive and significant impact on financial performance of MSMEs out of the nine BMC components. In this context, the efficiency in cost management significantly contributed to the improvement of financial performance. Other components such as Channels, Customer Relationships, Customer Segments, Key Activities, Key Partnerships, Key Resources, Revenue Streams, and Value Propositions did not have a significant impact on financial performance. Therefore, MSMEs in Kudus Regency were expected to optimize the implementation of the components to have a greater impact on financial performance. The practical implications were that MSMEs should focus more on efficient Cost Structure management as a primary strategy to enhance financial performance.